Contribution to the Cahier: Replacing the old heroes: Beauvoir’s defence of the existentialist protagonist - Ruonakoski, Erika (Sapere Aude, 2014)
In her article “Anciens et nouveaux héros”, included in L’Herne collection of texts by and on Simone de Beauvoir, Beauvoir elucidates the birth of the metaphysical novel and protagonists typical to it against the backdrop of the French psychological novel. Beauvoir’s descriptions shed light on the post-war literary scene in France as well as on her own stylistic ideals. Protagonists of the metaphysical novel are, according to Beauvoir, defined by their attitudes towards basic metaphysical problems rather than by their temperament or social position.